2005
DOI: 10.1117/12.625422
|View full text |Cite
|
Sign up to set email alerts
|

Engineering meter-scale laser resistant coatings for the near IR

Abstract: Laser resistant coatings are needed for beam steering (mirrors), pulse switching (polarizers), and high transport efficiency on environmental barriers (windows / lenses) on large laser systems. A range of defects limit the exposure fluence of these coatings. By understanding the origin and damage mechanisms for these defects, the deposition process can be optimized to realize coatings with greater laser resistance. Electric field modeling can provide insight into which defects are most problematic. Laser damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The NIF laser contains approximately 7500 large optics [8][9][10][11][12][13][14][15][16][17][18]. These optics are sized depending on their incident angle for the 37 × 37 cm square aperture beams.…”
Section: National Ignition Facility Opticsmentioning
confidence: 99%
“…The NIF laser contains approximately 7500 large optics [8][9][10][11][12][13][14][15][16][17][18]. These optics are sized depending on their incident angle for the 37 × 37 cm square aperture beams.…”
Section: National Ignition Facility Opticsmentioning
confidence: 99%
“…For example in the laser fusion apparatus at the National Ignition Facility (NIF) of Lawrence Livermore National Laboratories (LLNL), any external reflections or scattered light from the lasing windows or system lenses, gratings, and debris shields, adds spatial noise to the beam, limiting the ability of the system to focus enough power onto the target gas-filled pellets [1][2][3] . In other medical and industrial laser-based tools, reflected light can damage sensitive equipment such as imaging detectors or even components of the laser source itself such as pump laser diodes.…”
Section: Introductionmentioning
confidence: 99%
“…[1-2] Moreover, a recent study has shown that substrate scratches and impurities generated from surface finishing of the BK7 substrate can also lead to laser-induced damage on the multilayer coating. [3][4] Substrate scratches on the optic surface are inevitably created during the final shaping of the component through abrasive cutting, grinding and final polishing. Earlier studies have shown that substrate scratches on fused silica substrates act as precursors and lead to laser damage by inducing sub-bandgap absorption [5][6] which can be reduced by chemical etching of the substrate to improve optic performance.…”
Section: Introductionmentioning
confidence: 99%